12TH CONFERENCE ON HALOPHILIC MICROORGANISMS “HALOPHILES 2019”, 24‐28 JUNE 2019, CLUJ‐NAPOCA - multiple authors (Studia Universitatis Babeș-Bolyai. Biologia, 2019)
12TH CONFERENCE ON HALOPHILIC MICROORGANISMS “HALOPHILES 2019”, 24‐28 JUNE 2019, CLUJ‐NAPOCA: BOOK OF ABSTRACTS.